Composite democratic legitimation in Europe: The role of transparency and access to information - Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
The European Union is a composite democracy (Heritier 1999a; Benz 1998; Auel et al 2000; Manin 2000). It is comprised of diverse elements of democratic legitimation: the vertical legitimation through parliamentary representation in the EP; executive representation through delegates of democratically-elected governments in the Council of Ministers; horizontal mutual control among member states; associative and experts' representation (delegation) in policy networks (Benz 1998); and, finally, individual rights based legitimacy. Together these elements paint a variegated picture of the reality of democratic legitimation in Europe. The individual elements have not been developed and linked in a systematic and consistent way; rather, they have emerged from a series of pragmatic decisions, made among the range of limited possibilities allowed for by the unanimity requirements of the intergovernmental conferences or as a result of incremental individual initiatives of the different European decision-making bodies. As a consequence, it does not come as a surprise that some elements are incompatible with each other, both with respect to their primary goals and their modes of operation. The nature, reasons and consequences of this type of incompatibility or compatibility are at the centre of this article. Of particular interest is the question of relationship between the legimatory components of access to information and transparency, on the one hand, and the element of negotiative democracy that is, governance in policy networks, as an ubiquitous mode of governance in Europe, on the other. While transparency and access to information stress the input-oriented goals of democratic legitimation, that is the right to know who makes which decisions when, associative representation and negotiative democracy emphasise the output-oriented goals of democratic legitimation, that is government legitimation through policy performance accommodating the widest possible scope of interests. Both input- and output-oriented legitimation are important and have to be viewed in their reciprocal relationship.
Keywords: 330